GENETIC VARIABILITY OF NATURAL POPULATIONS OF CHESTNUT Bertholletia excelsa IN THE MADRE DE DIOS REGION, PERUVIAN AMAZON - PANDURO, Hugo (2022)
Population genetic variability of Brazil nut Bertholletia excelsa in the Madre de Dios region was determined by analyzing 11 microsatellites markers in a total of 108 trees. The global results showed a great allelic diversity (89 alleles, with a mean of 8.09 alleles per locus), at the localities level the highest allelic richness was found in Iberia (AR = 4.82) and the lowest in Itahuania (AR = 3.64), this the same localities were the only ones that presented an excess of heterozygotes. The results of the correspondence factor analysis (AFC) show a strong genetic overlap between most of the analyzed localities. The results of the Fixation Index (Fst) show that the localities of Iñapari and Iberia are more related to each other (Fst = 0.048), but slightly differentiated with the other localities (the values of Fst with the other localities varied between -0.001 to 0.193). The dendrogram based on the genetic distance of Nei (1978) shows that the 11 localities are forming three different genetic groupings, (A): Amigos, Pukiri, Itahuania and Manuripe; (B): Heath, Tambopata, Virgen del Carmen, Pariamanu, Iberia and Iñapari; and (C) made up only of the Alert locality. The groups within the clusters could be attributed to the few physical barriers between the localities within each cluster, while the differentiations between the clusters could be related to the presence of rivers between these groups, which could constitute insurmountable physical barriers to for gene flow between these clusters.